2014
DOI: 10.3184/174751914x13896291543361
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of Some Novel Symmetrical and Unsymmetrical Pyridine bis-1,2,4-triazoles and bis-1,3,4-thiadiazoles

Abstract: A series of novel bis-1,2,4-triazoles and bis-1,3,4-thiadiazoles bearing pyridine rings was synthesised, by multistep reaction sequences, in good to high yields. Reaction of pyridine-2,5-bis-and pyridine-2,6-bis-carbohydrazides with alkyl-or arylisothiocyanates gave the corresponding bis(thiosemicarbazide) derivatives, which could be cyclised under strongly basic conditions to give novel pyridine bis(1,2,4-triazole-3-thiols). However, under strongly acidic conditions the corresponding bis(2-amino-1,3,4thiadiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although compounds 2f and 2g were synthesized by a different method in the literature, it was seen that the 1 H-NMR spectra results were very close. [34,48] The resulting 13 C-NMR spectrum of compound 2d is given in Figure 1, and the resulting 1 H-NMR spectrum is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although compounds 2f and 2g were synthesized by a different method in the literature, it was seen that the 1 H-NMR spectra results were very close. [34,48] The resulting 13 C-NMR spectrum of compound 2d is given in Figure 1, and the resulting 1 H-NMR spectrum is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…All 1 H‐NMR spectra of the synthesized compounds are provided in the supplementary file. Although compounds 2f and 2g were synthesized by a different method in the literature, it was seen that the 1 H‐NMR spectra results were very close [34,48] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray single crystallography of 1,2,4‐triazole has shown that N–H…S hydrogen bonds are dimering and linked into chains . Furthermore, bis‐1,2,4‐triazoles and bis‐1,3,4‐thiadiazoles bearing pyridine rings have been reported by Foroughifar et al …”
Section: Introductionmentioning
confidence: 92%